(untitled) (American Journal of Management, 2022)
Dirty work involves tasks that are considered disgusting or degrading. Individuals engaged in dirty work are often stigmatized, and this stigma may negatively affect the workers’ job-related attitudes. Although dirty work is often cast in a negative light, we explore an aspect of jobs that might lessen the detrimental effects of performing dirty work: invisibility. Using a sample of 329 working adults, we investigate the impact of invisibility on job satisfaction and occupational identification of marginalized dirty workers. Results indicate that performing dirty work, and being marginalized, each negatively impact job-related attitudes. In dirty occupations, relationships were weaker for employees reporting higher levels of invisibility with invisible employees reporting higher levels of occupational identification than their more visible counterparts. These findings shed new light on developing positive workplace experiences by suggesting that invisibility may be the key to reducing the stigmas associated with dirty work. Theoretical implications, directions for future research, and practical implications are discussed.